Treatment patterns in patients with acute myeloid leukemia in the United States: a cross-sectional, real-world survey. (4th May 2019) - Medeiros, Bruno C.; Pandya, Bhavik J.; Hadfield, Anna; Pike, James; Wilson, Samuel; Mueller, Cynthia; Bui, Cat N.; Flanders, Scott C.; Rider, Alex; Horvath Walsh, L. Elise
Abstract: Objective: The aim of this analysis was to examine treatment patterns in patients with acute myeloid leukemia (AML) in routine clinical practice in the United States, including factors influencing the choice of front-line treatment intensity and the effect of age and treatment line. Methods: We used data from the Adelphi AML Disease Specific Programme, a real-world, cross-sectional survey conducted in 2015. Physicians completed patient record forms providing patients' demographic and clinical characteristics. Results: In total, 61 academic, non-academic, and office-based hematologists and hematology/oncology specialists provided data on 457 patients with AML; 284 had ≥20% blasts (World Health Organization defined AML) and were included in the analysis. In the front-line setting, 60% of patients received high-intensity therapy, most commonly cytarabine plus anthracycline; the most common low-intensity treatments were hypomethylating agents. Primary drivers for selecting high-intensity versus low-intensity treatment were age, performance status and comorbidities; 67%, 64% and 61% of physicians stated they would prescribe high-intensity treatment to patients aged <65 years, with good performance status or no comorbidities, respectively. In practice, patients aged <60 years were more likely to receive high-intensity induction treatment (high vs. low intensity by age p < .0001). In a selected cohort of relapsed/refractory patients, 69% of patients received high-intensity therapy (78% of patients aged <60 years and 57% of patients aged ≥60 years). Conclusions: Most patients in this analysis of real-world survey data received well established, front-line induction therapies. Treatment intensity was determined by age, comorbidities and performance status, as recommended by guidelines.